Novel single-source precursors for SiBxCyNz film deposition. (19th September 2017) - Merenkov, Ivan S.; Gostevskii, Boris A.; Krasnov, Pavel O.; Basova, Tamara V.; Zhukov, Yuri M.; Kasatkin, Igor A.; Sysoev, Sergey V.; Kosyakov, Victor I.; Khomyakov, Maksim N.; Kosinova, Marina L.
Abstract : A novel type of single-source CVD precursor – Me3 SiCCB[N(SiMe3 )2 ]2 – has been synthesized and successfully tested for the first time in SiBCN film deposition. Abstract : Novel CVD precursors for SiB x C y N z film deposition such as HCCB[N(SiMe3 )2 ]2, MeB[N(SiMe3 )2 ]2 and Me3 SiCCB[N(SiMe3 )2 ]2 were synthesized. The structure and composition of the compounds were investigated with NMR, FTIR, Raman spectroscopies and CHN-analysis. Comparison of theoretical and experimental FTIR and Raman data was performed. Thermogravimetric analysis and the static tensimetry method with a glass membrane null manometer demonstrated that Me3 SiCCB[N(SiMe3 )2 ]2 is the most suitable CVD precursor. The formation of SiB x C y N z films was predicted using thermodynamic modelling at a temperature below 1600 K in the total pressure range of 0.27–1333 Pa. The films of chemical composition Si23.7 B8.3 C51.4 N9.6 O7 were deposited by low-pressure chemical vapour deposition (LPCVD) and their morphology and mechanical properties were investigated. The amorphous SiB x C y N z films with a smooth surface exhibited hardness, Young's modulus and elastic recovery equal to 17.5 ± 0.9 GPa, 176 ± 11 GPa and 61 ± 2%, respectively.